2011
DOI: 10.1016/j.cbpc.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and functional characterization of proinflammatory acidic phospholipase A2 from Bothrops leucurus snake venom

Abstract: In the present study, an acidic PLA(2), designated Bl-PLA(2), was isolated from Bothrops leucurus snake venom through two chromatographic steps: ion-exchange on CM-Sepharose and hydrophobic chromatography on Phenyl-Sepharose. Bl-PLA(2) was homogeneous on SDS-PAGE and when submitted to 2D electrophoresis the molecular mass was 15,000Da and pI was 5.4. Its N-terminal sequence revealed a high homology with other Asp49 acidic PLA(2)s from snake venoms. Its specific activity was 159.9U/mg and the indirect hemolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 63 publications
3
17
0
10
Order By: Relevance
“…Several PLA 2 s have been identified from Bothrops leucurus venom including one acidic [7], one basic phospholipase A 2 and phospholipase A 2 homologous K49 [8]. This diversity of PLA 2 , found in the venom of Bothrops leucurus , agrees with studies that show marked ontogenetic and individual venom variations [1].…”
Section: Introductionsupporting
confidence: 71%
“…Several PLA 2 s have been identified from Bothrops leucurus venom including one acidic [7], one basic phospholipase A 2 and phospholipase A 2 homologous K49 [8]. This diversity of PLA 2 , found in the venom of Bothrops leucurus , agrees with studies that show marked ontogenetic and individual venom variations [1].…”
Section: Introductionsupporting
confidence: 71%
“…Similarly, Bl-PLA 2 isolated from Bothrops leucurus (Nunes et al, 2011), a PLA 2 from C. oreganus abyssus (Martins et al, 2014), and ColTx-I were able to induce local inflammatory responses reaching maximum values in the first 30 min. Basic biochemical mechanisms behind paw edema mainly involve phospholipid hydrolysis with subsequent release of biologically active fatty acids and platelet activating factor or mast cell histamine release (Teixeira et al, 2009) and/or the interaction of the pharmacological domain, independently of the catalytic site (Zuliani et al, 2005) (Fig.…”
Section: Numbermentioning
confidence: 92%
“…[15], demonstrated that BmooTX-I was able to damage plasmatic membrane formed by some types of phospholipids, mainly phosphatidylcholine, which were hydrolyzed by BmooTX-I producing free fatty acids and lysophospholipids, causing cellular damage. By the contrary, Bl-PLA2 not evidenced cell viability damage on human peripheral blood mononuclear cells [18]. In the same way, BaspPLA2-II did not caused damage on cell membranes of skeletal C2C12 myoblasts in culture [7].…”
Section: Discussionmentioning
confidence: 73%